Handbook of research on emerging developments and environmental impacts of ecological chemistry - Duca, Gheorghe 1952-; Vaseashta, Ashok 1954- (IGI Global, 2020)
"This book examines the environmental impacts of ecological chemistry"--
Keywords: Green chemistry